Implementation of the IPK® Esports Method in a Professional League of Legends Team: A Pilot Study on Circadian Monitoring, Neurofunctional Recovery, and Cognitive Performance - Juan Carlos Andrade; Mikeldi Aguirre Berasategui (Sumatera Medical Journal, 2026)
Introduction: Esports athletes are exposed to neurophysiological stress, irregular sleep patterns, and cognitive overload, which can impair performance and health. The IPK Esports® Method integrates daily wellness tracking, circadian rhythm monitoring, and neurofunctional physiotherapy. Objective: To describe the implementation of the IPK Esports® Method in a professional League of Legends team, highlighting a one-time 7-day circadian rhythm assessment with Kronowise® and the application of individualized neurophysiological interventions. Methods: This descriptive study was conducted during the preparation and regular competitive season. Players completed daily wellness questionnaires. Weekly neurotraining sessions were implemented to enhance motor control and cognitive performance. A single 7-day assessment with Kronowise® recorded circadian parameters and estimated sleep. Post-training, players underwent reaction tests. Based on data, customized physiotherapy interventions were applied. Results: Circadian analysis showed delayed sleep onset, fragmented sleep, and high pre-sleep blue light exposure, informing targeted sleep hygiene strategies. Participants with higher circadian stability tended to have lower reaction time variability. Given the pilot sample (n=2), findings are exploratory, and no inferential analysis was conducted. Conclusion: The IPK Esports® Method enables a personalized, data-driven approach to optimize health, recovery, and performance in esports athletes.